2022
DOI: 10.1098/rstb.2021.0175
|View full text |Cite
|
Sign up to set email alerts
|

The naturalistic approach to laughter in humans and other animals: towards a unified theory

Abstract: This opinion piece aims to tackle the biological, psychological, neural and cultural underpinnings of laughter from a naturalistic and evolutionary perspective. A naturalistic account of laughter requires the revaluation of two dogmas of a longstanding philosophical tradition, that is, the quintessential link between laughter and humour, and the uniquely human nature of this behaviour. In the spirit of Provine's and Panksepp's seminal studies, who firstly argued against the anti-naturalistic dogmas, here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Recent research provides strong evidence for various animal calls being analogous to laughter (Palagi, Caruana & de Waal, 2022). Modern phylogenetic analysis has shown that laughter dates back to at least the common ancestor of apes and humans, some 10–16 million years ago (Mya) (Ross, Owren & Zimmermann, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research provides strong evidence for various animal calls being analogous to laughter (Palagi, Caruana & de Waal, 2022). Modern phylogenetic analysis has shown that laughter dates back to at least the common ancestor of apes and humans, some 10–16 million years ago (Mya) (Ross, Owren & Zimmermann, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An opinion piece provides a unifying framework across the different disciplines also suggesting further ideas to expand the knowledge through a comparative approach (Palagi et al . [ 1 ]). Then four reviews frame laughter studies in the fields of anthropology (Dunbar [ 2 ]), ethology (Davila-Ross & Palagi [ 3 ]), psychology (Scott et al .…”
Section: Introductionmentioning
confidence: 99%